HYDROLOGICAL EFFICIENCY OF WATER STORAGE TECHNOLOGIES IN ARID REGIONS - Eshmanov Husniddin Narzulla o’g’li (Ta’lim innovatsiyasi va integratsiyasi, 2025)
Abstract: This study investigates the hydrological efficiency of various water storage technologies implemented in arid and semi-arid regions to mitigate water scarcity. It examines how these technologies affect water conservation, groundwater recharge, and surface water availability. Field measurements and hydrological modeling were used to assess the performance of reservoirs, check dams, and soil moisture retention methods. The results demonstrate significant improvements in water availability and ecosystem sustainability. Recommendations for optimizing water storage infrastructure to enhance hydrological efficiency in dry environments are discussed.